Networklike Propagation of Cell-Level Stress in Sheared Random Foams - Evans, Myfanwy; Kraynik, Andrew M.; Reinelt, Douglas A.; Mecke, Klaus; Schröder-Turk, Gerd (Physical Review Letters, 2013)
Quasistatic simple shearing flow of random monodisperse soap froth is investigated by analyzing SURFACE EVOLVER simulations of spatially periodic foams. Elastic-plastic behavior is caused by irreversible topological rearrangements (T1s) that occur when Plateau's laws are violated; the first T1 determines the elastic limit and frequent T1 avalanches sustain the yield-stress plateau at large strains. The stress and shape anisotropy of individual cells is quantified by Q, a scalar derived from an interface tensor that gauges the cell's contribution to the global stress. During each T1 avalanche, the connected set of cells with decreasing Q, called the stress release domain, is networklike and nonlocal. Geometrically, the networklike nature of the stress release domains is corroborated through morphological analysis using the Euler characteristic. The stress release domain is distinctly different from the set of cells that change topology during a T1 avalanche. Our results highlight the connection between the unique rheological behavior of foams and the complex large-scale cooperative rearrangements of foam cells that accompany distinctly local topological transitions.